FORMATIVE ELECTRONIC ASSESSMENTS DURING COVID-19 LOCKDOWN IN SECOND PHASE MEDICAL UNDERGRADUATES - PALAPPALLIL, DHANYA SASIDHARAN; SUJATHA, DEEPA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Electronic learning and assessment was embraced in medical education worldwide following the COVID-19 pandemic. This study was done to determine the perceptions of medical undergraduates on formative electronic assessments conducted during COVID-19 lockdown and to estimate the mean marks scored in these assessments. Methods: This was a descriptive study done for a period of 3 months on online platform. Six online formative assessments were conducted on Google Forms or Kahoot. A questionnaire was administered as Google Form to collect the perceptions of the participants on perceived ease of use of platform, attitude, and practice adopted in online assessments. Data were analyzed using SPSS 16. Results: The response rate was 97.7%. Kahoot was perceived to be easier with lesser technical glitches and privacy concerns as compared to Google, while it was equivocal in terms of access assessment links, output storage, display clarity, overall user interface, network issues, need for computer literacy, and eyestrain caused. The participants had a positive attitude regarding the usefulness of online assessments however majority liked the traditional assessments more than the online assessments. While less than one-third (22%) had copy pasted some answers, more than half (54.4%) had referred to internet and more than three quarter (79.6%) had referred to textbooks/power points/notes while attending online assessments. Conclusion: The participants felt that Google Forms and Kahoot were comparable online assessment tools except for difficulty in filling, privacy concerns, and technical issues on Google Forms. The usefulness of online assessments was embraced by the participants but they felt that the traditional assessments were to be continued, while attending online assessments some students had referred to the internet or study materials.